Integration of SWOT Analysis - Supply and Demand Approach for Simalungun Regency Culinary Tourism Destination Development Strategy - Indra, Rama; Sibarani, Robert; Revida, Erika; Rujiman, Rujiman (Journal of Ecohumanism, 2024)
There is a need to develop local culinary potential as a tourist attraction in Simalungun Regency. This is done to bring as many tourists as possible to Simalungun Regency through culinary tourism. The locus of this research is 4 tourist destinations in Simalungun Regency, namely Haranggaol, BIS, Sibaganding, and Parapat. Regional planning is a process of knowing and analyzing current conditions, forecasting the development of various factors, estimating limiting factors, setting goals and objectives to be achieved, determining steps to achieve goals, and determining locations and various activities to be carried out. One of the approaches taken to carry out the regional planning process is SWOT and Supply and Demand Analysis. The research was conducted over several months involving informants to obtain valid information. Based on the results of interviews addressed directly to informants, currently the attractions offered to visiting tourists are natural attractions in the form of scenery. Therefore, the existence of photo spots is the most desirable because of their natural beauty so it is worth displaying on social media pages such as Instagram and Facebook. Good tourist attractions must be able to bring in many tourists and hold them for a long time, assuming that the greater the profit expected from their presence by providing satisfaction to tourists. Activities and objects that are attractions must be in good condition, both attractions in the form of activities such as dances, as well as attractions in the form of objects, such as temples, krises, and so on, the way of presentation must be appropriate because tourist attractions are presented in front of visitors to tourist objects which will be said to be successful if they cause impressions and satisfaction to tourists. Tourism objects must also be integrated with other tourism requirements such as services and transportation. The identification of tourist attractions and existing supporting facilities/infrastructure in DTW Haranggaol, Bukit Indah Simarjarunjung, Sibaganding, and Parapat, Simalungun Regency was carried out using data on existing tourist attractions in DTW Haranggaol, Bukit Indah Simarjarunjung, Sibaganding, and Parapat, Simalungun Regency obtained from field observations and the results of the Quantitative - Two Steps Questionnaire round I method. The condition data is not only obtained from the results of field observations but also from the average value of respondents' answers to the attraction conditions in round II. The existence of amenities is one of the factors that support the activities of visitors to DTW Haranggaol, Bukit Indah Simarjarunjung.